CHEMICAL ANALYSIS OF MEFENAMIC ACID IN (Montalin) HERBAL MEDICINE CIRCULATING IN YOGYAKARTA CITY - Abibatul Azizah; Bariqna'im Katon Haryanggita; Niam Mardiah Giseliani Wirata Kusuma; Ferdinan Khan Sondak (DAS Institute, 2023)
Jamu for rheumatic pain is one of the most popular herbal medicines in Indonesia, and jamu manufacturers often add pharmaceutical chemicals (BKO) to make the treatment effect more effective. One of the BKOs added is mefenamic acid. The addition of mefenamic acid can cause dangerous side effects such as convulsions and even coma. This study aims to determine the content of mefenamic acid BKO in herbal sciatica preparations circulating in the Yogyakata area. The purpose of this study was to determine the validity of the UV spectrophotometric method in the analysis of mefenamic acid content in pure mefenamic acid tablets determined based on certain parameters. Validation parameters including accuracy, precision, limit of detection (LOD) and limit of quantification (LOQ). Results of this method validation test showed limit of quantity (LOQ) 0,244476 ppm and limit of detection (LOD) 0,073343 ppm.